Ecological value of retaining pyrophytic oaks in longleaf pine ecosystems. Issue 3 (21st March 2014) - Hiers, J. Kevin; Walters, Jeffrey R.; Mitchell, Robert J.; Varner, J. Morgan; Conner, L. Mike; Blanc, Lori A.; Stowe, Johnny
ABSTRACT Species intolerant to fire, defined as lacking adaptations needed to establish dominance in a frequently burned landscape, are found within fire‐prone ecosystems globally. Such species are frequently targeted for reduction or eradication to further conservation or restoration of biological diversity because the dominant paradigm in restoration of fire‐dependent communities is to reduce the dominance or eliminate fire‐intolerant invaders. To explore this paradigm, we examined the role of oaks (Quercus spp.) within fire‐dependent upland and sandhill longleaf pine (Pinus palustris) ecosystems of the southeastern United States. These pine‐oak ecosystems have among the highest levels of biodiversity in the temperate zone. This diversity is inextricably linked to a frequent fire regime and includes many species readily top‐killed by fire, particularly oaks, which were common in the early settlement landscape. In examining the diversity of oak species found within longleaf pine ecosystems, we identify a group of pyrophytic oaks and show that these oaks are critical components of sandhill and other longleaf pine ecosystems, and their occurrence should be considered as part of conservation and restoration goals. Providing a better understanding of the ecological role of such species will benefit conservation management and strategic planning in fire‐prone southeastern ecosystems and more broadly where fire is used as a management tool. © 2014 The Wildlife Society.